Consumer Behavior in Marketing 4.0: Social Media Marketing and Website Marketing on Purchasing Decisions through TAM As a Mediating Variable - Andika Baskara; Nurhayati (International Journal of Social Science and Business, 2023)
Today's marketing 4.0 affects the way consumers purchase decisions. Therefore, it needs to find out factors that can increase purchase decisions. This research aims to determine social media and website marketing on TAM with the use of TAM as a mediating variable. This research is quantitative research conducted on 100 random consumers using simple random sampling. Meanwhile, the data is collected using a questionnaire spread along consumers that are considering and who already have a motorcycle in Semarang City and analyzed using a Structural Equation Model (SEM) approach assisted by smart PLS applications. From the results, it is seen that there is a relationship between TAM on purchase decision, website marketing on purchase decision, social media and website marketing on TAM, and the relationship between social media and website marketing is increased through TAM. Therefore, every company needs to maximally enhance its website marketing and TAM to have consumers check out the products that the company owns. However, because this research only involves three variables to enhance the purchase edition, further research that involves other variables needs to be conducted.